(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses the issues of studying the functional reserves of the athletes’ body in the conditions of the Republic of Karakalpakstan. The authors noted that the functional reserves of the body of athletes engaged in various sports provide the possibility of changing the functional activity of its structural elements, their ability to interact with each other to adapt to the effects of environmental factors on the body.